The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1242/bio.036103
|View full text |Cite
|
Sign up to set email alerts
|

Extending chemical perturbations of the ubiquitin fitness landscape in a classroom setting reveals new constraints on sequence tolerance

Abstract: Although the primary protein sequence of ubiquitin (Ub) is extremely stable over evolutionary time, it is highly tolerant to mutation during selection experiments performed in the laboratory. We have proposed that this discrepancy results from the difference between fitness under laboratory culture conditions and the selective pressures in changing environments over evolutionary timescales. Building on our previous work (Mavor et al., 2016), we used deep mutational scanning to determine how twelve new chemical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…In previous deep mutational scanning experiments, stringent selection typically revealed many disadvantageous mutations ( Garst et al, 2017 ; Jiang et al, 2013 ; Mavor et al, 2016 ; Mavor et al, 2018 ; Stiffler et al, 2015 ). In contrast, the most striking observation under our conditions is the large fraction of advantageous mutations (red, Figure 1D ): 736 of 3161 possible variants were advantageous (23.3%), and wild-type DHFR only ranked 1203 rd (although 467 of the 1202 higher-ranking variants fall into the WT-like interval).…”
Section: Resultsmentioning
confidence: 99%
“…In previous deep mutational scanning experiments, stringent selection typically revealed many disadvantageous mutations ( Garst et al, 2017 ; Jiang et al, 2013 ; Mavor et al, 2016 ; Mavor et al, 2018 ; Stiffler et al, 2015 ). In contrast, the most striking observation under our conditions is the large fraction of advantageous mutations (red, Figure 1D ): 736 of 3161 possible variants were advantageous (23.3%), and wild-type DHFR only ranked 1203 rd (although 467 of the 1202 higher-ranking variants fall into the WT-like interval).…”
Section: Resultsmentioning
confidence: 99%
“…DMS also screens proteins for improved drug binding, antibody affinity, using non-native chemical stresses, or non-proteinogenic amino acids, and on synthetic proteins [19][20][21][22][23][24][25][26]. Finally, DMS share objectives with directed evolution, benefiting protein engineering [14].…”
Section: Introductionmentioning
confidence: 99%
“…By conducting screens in the presence of different chemical additives, however, Fraser and co-workers showed that virtually every residue in ubiquitin, with the exception of two, can be sensitized to mutation under a particular selection condition (Figure 2C). These results demonstrate that the evolutionary trajectory of ubiquitin is shaped by a necessity to function under different environmental conditions, in which ubiquitin may engage in distinct sets of interactions 69,70 .…”
Section: Interaction Specificity During Cell Signalingmentioning
confidence: 78%
“…The diversity of interactions made by ubiquitin is one likely explanation for its strict conservation. This hypothesis was tested in a series of studies using deep mutational scans of ubiquitin in yeast 6870 . Under particular selection conditions, most positions in ubiquitin are remarkably tolerant to amino acid substitution.…”
Section: Interaction Specificity During Cell Signalingmentioning
confidence: 99%